Maternal Vitamin D3 Supplementation during the Third Trimester of Pregnancy: Effects on Infant Growth in a Longitudinal Follow-Up Study in Bangladesh - Roth, Daniel E.; Perumal, Nandita; Al Mahmud, Abdullah; Baqui, Abdullah H. (The Journal of pediatrics, 2013)
To estimate the effects of prenatal vitamin D supplementation on infant growth in Dhaka, Bangladesh. Longitudinal follow-up of infants born at term or late preterm (≥34 weeks) to participants in a randomized double-blind trial of maternal third-trimester vitamin D3 (35 000 IU/wk; vitamin D ) vs placebo. Anthropometry was performed at birth, 1, 2, 4, 6, 9, and 12 months of age. The primary analysis (n = 145 overall; n = 134 at 1 year) was a comparison of mean length-for-age z-score (LAZ) based on World Health Organization standards. LAZ was similar between groups at birth, but 0.44 (95% CI, 0.06-0.82) higher in vitamin D vs placebo at 1 year, corresponding to a sex-adjusted increase of 1.1 cm (95% CI, 0.06-2.0). Mean change in LAZ from birth to 1 month was significantly greater in vitamin D (0.53 per month) vs placebo (0.19 per month; P = .004); but there was no significant divergence thereafter. In longitudinal (repeated-measures) analysis, average LAZ during infancy was 0.41 higher in vitamin D vs placebo (95% CI, 0.11-0.71, P = .01). Stunting was less common in vitamin D (17% of infants were ever stunted) vs placebo (31%; P = .049). Other anthropometric indices were similar between groups. Maternal vitamin D3 supplementation (35 000 IU/wk) during the third trimester of pregnancy enhanced early postnatal linear growth in a cohort of infants in Bangladesh.